The association of clozapine treatment periods with incidence of exposure to assault and head injuries - a cohort study of electronic health records - Kingston, Francesca; Stewart, Robert; Govind, Risha; Jewell, Amelia; Bhavsar, Vishal; MacCabe, James H. (Frontiers in Psychiatry, 2026)
People with schizophrenia experience violent victimization, and interventions to reduce this risk are needed. We tested the association of clozapine treatment with risk of exposure to assault and head injuries using electronic health records linked to a national clozapine treatment register and to national hospitalization data. The unadjusted incidence rate ratio (IRR) for clozapine treatment on exposure to assault and head injuries was 0.44 (95% confidence interval [CI]: 0.28-0.69). This effect remained statistically significant after covariate adjustment (0.46 (0.29-0.74); 0.40 (0.22-0.71) in men; 0.64 (0.29-1.43) in women. Clozapine treatment was thus associated with a substantially reduced risk of exposure to assault and head injuries.